Podophyllotoxin and its derivatives: Potential anticancer agents of natural origin in cancer chemotherapy - Motyka, Sara; Jafernik, Karolina; Ekiert, Halina; Sharifi-Rad, Javad; Calina, Daniela; Al-Omari, Basem; Szopa, Agnieszka; Cho, William C. (Biomedicine & pharmacotherapy, 2023)
The use of plant secondary metabolites has gained considerable attention among clinicians in the prevention and treatment of cancer. A secondary metabolite isolated mainly from the roots and rhizomes of Podophyllum species (Berberidaceae) is aryltetralin lignan - podophyllotoxin (PTOX). The purpose of this review is to discuss the therapeutic properties of PTOX as an important anticancer compound of natural origin. The relevant information regarding the antitumor mechanisms of podophyllotoxin and its derivatives were collected and analyzed from scientific databases. The results of the analysis showed PTOX exhibits potent cytotoxic activity; however, it cannot be used in its pure form due to its toxicity and generation of many side effects. Therefore, it practically remains clinically unusable. Currently, high effort is focused on attempts to synthesize analogs of PTOX that have better properties for therapeutic use e.g. etoposide (VP-16), teniposide, etopophos. PTOX derivatives are used as anticancer drugs which are showing additional immunosuppressive, antiviral, antioxidant, hypolipemic, and anti-inflammatory effects. In this review, attention is paid to the high potential of the usefulness of in vitro cultures of P. peltatum which can be a valuable source of lignans, including PTOX. In conclusion, the preclinical pharmacological studies in vitro and in vivo confirm the anticancer and chemotherapeutic potential of PTOX and its derivatives. In the future, clinical studies on human subjects are needed to certify the antitumor effects and the anticancer mechanisms to be certified and analyzed in more detail and to validate the experimental pharmacological preclinical studies.